On the optimal reconstruction of the values of operators - Korneichuk, N. P. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
For a continuous operator А: X → Y, we formulate the problem of the optimal renewal of values Аx, x X by decreasing the uncertainty domain by using an information μ_k(x), k = 1, 2, ...,, where μ_k are continuous functionals, defined on the space X. Specific results are obtained for some integral operators in functional spaces.